CeO2 Nanorods Embedded in Ni(OH)2 Matrix for the Non-Enzymatic Detection of Glucose - Yongjian Li; Panpan Guan; Fucheng Yu; Wei Li; Xiaoling Xie (Nanomaterials, 2017)
The electrode based on cerium oxide (CeO2) nanorods embedded in nickel hydroxide (Ni(OH)2) matrix were prepared and used for detecting glucose non-enzymatically. The materials were characterized by X-ray diffraction, transmission electron microscopy (TEM), and so on. The results indicate that the response of CeO2/Ni(OH)2 nanocomposite are significantly improved due to the synergetic effect between CeO2 and Ni(OH)2. The optimum CeO2/Ni(OH)2 nanocomposite electrode exhibits a detection range from 2 μM to 6.62 mM, a sensitivity of 594 μA mM−1 cm−2, an estimated detection limit of 1.13 μM, and a response time less than 5 s. In addition, this biosensor also shows good selectivity, long term stability, and accurate measurement in juice on sale.